Traditional Chinese herbal medicine: harnessing dendritic cells for anti-tumor benefits - Shen, Mengyi; Li, Zhen; Wang, Jing; Xiang, Hongjie; Xie, Qi (Frontiers in Immunology, 2024)
Chinese Herbal Medicine (CHM) is being more and more used in cancer treatment because of its ability to regulate the immune system. Chinese Herbal Medicine has several advantages over other treatment options, including being multi-component, multi-target, and having fewer side effects. Dendritic cells (DCs) are specialized antigen presenting cells that play a vital part in connecting the innate and adaptive immune systems. They are also important in immunotherapy. Recent evidence suggests that Chinese Herbal Medicine and its components can positively impact the immune response by targeting key functions of dendritic cells. In this review, we have summarized the influences of Chinese Herbal Medicine on the immunobiological feature of dendritic cells, emphasized an anti-tumor effect of CHM-treated DCs, and also pointed out deficiencies in the regulation of DC function by Chinese Herbal Medicine and outlined future research directions.